Lyrik? En refleksion over den lyriske genres aktuelle status - Mønster, Louise (Passage - Tidsskrift for litteratur og kritik, 2016)
Louise Mønster: “Poetry? A Reflection on the Status of the Poetic Genre” The article raises the question of genre in relation to contemporary poetry. The point of departure is the mismatch between the ordinary understanding of poetry as a short literary form that expresses the experiences, thoughts and feelings of a subject, and the actual ways in which much contemporary poetry unfolds. The article discusses why it is still relevant to sustain the concept of poetry, and it points out four factors that are believed to play an important role in explaining why the established concept of poetry has come under pressure in recent years. These factors have to do with mediatization, literary culture, forms of publication and increased politicization.